The impact of digitalization of accounting systems on the operational efficiency of MSMEs in the digital economy era - Refdi, Refdi; Hasibuan, Masnilam; Triyono, Triyono; Rukmana, Indra Heri (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The rapid advancement of digital technology has driven the digitalization of accounting systems as a strategic tool to enhance the operational efficiency of micro, small, and medium enterprises (MSMEs) in the digital economy era. This study aims to analyze the impact of accounting system digitalization on MSMEs’ operational efficiency and to identify factors influencing its implementation. Using a qualitative library research method, this study systematically reviews relevant national and international literature published over the last decade. The findings indicate that digital accounting systems significantly improve time and cost efficiency through automation, enhance the accuracy and timeliness of financial information, and support more effective managerial decision-making. However, the effectiveness of digitalization is mediated by factors such as digital literacy, managerial support, innovation capability, and regulatory environment. This study concludes that accounting digitalization represents a strategic organizational transformation essential for improving MSMEs’ operational efficiency and competitiveness in the digital economy.